Engineered Microneedle System Enables the Smart Regulation of Nanodynamic Sterilization and Tissue Regeneration for Wound Management - Shiyang Lin; Zhongqi Cui; Qingqiong Luo; Chen Li; Yue Zhang; Fengjiao Yang; Yichuan Chen; Chuansheng Xu; Yan Gao; Shasha Zhao; Fenyong Sun; Dandan Shen; et al. (Advanced Science)
Abstract The healing of bacterial biofilm‐infected wounds is a complex process, and the construction of emerging therapeutic modalities that regulate the microenvironment to magnify therapeutic effects and reduce biotoxicity is still highly challenging. Herein, an engineered microneedle (MN) patch is reported to mediate the efficient delivery of black phosphorus nanosheets (BP NSs) and copper peroxide nanodots (CP NDs) for dual nanodynamic sterilization and methicillin‐resistant staphylococcus aureus (MRSA)‐infected wound healing. Results demonstrate that the system can eliminate biofilm, reduce cytotoxicity, promote angiogenesis and tissue regeneration by the multiple advantages of chemodynamic therapy (CDT), enhanced photodynamic therapy (PDT), and improved degradation process from BP NSs to phosphate for promoting cell proliferation. Notably, the balance between excellent photodynamic stability and rapid degradability of BP NSs is maintained, and the improved degradation mechanism of BP NSs is vividly elucidated by density functional theory (DFT)‐based molecular dynamics (MD) calculations. Furthermore, the transcriptional changes of treated MRSA‐infected skin are studied using RNA‐seq technology to reveal the potential therapeutic mechanism. As envisaged, the proposed MN patch provides a safe, easy, also highly effective approach to achieve the temporal regulation of sterilization and tissue regeneration for bacterial biofilm‐infected wounds.